Lifestyle as a Branding Strategy for the Sustainable Brand - Giancarlo Scozzese; Margherita Gelli (European Scientific Journal, ESJ, 2023)
The increasing need for concrete action to mitigate the effects of the climate crisis is pushing the younger generation towards more sustainable lifestyles to demand that companies pay more attention to the environment, human rights, and more general issues of social justice. Today, distrust of institutions is at an all-time high, and consumers expect more from the companies to which they are attached. At this point, brands can make a positive contribution to addressing these issues. On this basis, it becomes clear how important this can be for corporate strategy, as the companies that are able to inspire and earn long-term loyalty are the ones that are able to take on the role of point of reference in the society. The assumed role is crucial in the purchasing decisions of more conscious consumers and can be achieved, for example, through a brand position on a social issue or by offering a value system rather than a lifestyle proposition. It helps a brand that represents the lifestyle of a group of people driven by a strong desire to belong there and disrupt the status quo, to connect with customers and make its offer competitive. A lifestyle brand characterised by high symbolic power and a strong emotional connection with its target audience, by offering action to protect the environment, stimulates cultural change that appears critical in relation to hyper-consumption and the resulting environmental impact. This, however, enables its customers to gain greater satisfaction from their purchasing choices and represents a real opportunity to build a sustainable brand.